Effects of climate change on the breeding success of White-fronted Geese Anser albifrons flavirostris in west Greenland - Boyd, Hugh; Fox, Anthony D (Wildfowl, 2013)
Numbers of Greenland White-fronted Goose Anser albifrons flavirostris pairs breeding successfully have been falling since the 1980s, markedly so since the mid-1990s. The latter change coincides with a switch in the Atlantic Multidecadal Oscillation, associated with increased spring precipitation in west Greenland. During the 1960s to 1980s, breeding success amongst birds wintering on Islay, southwest Scotland, correlated positively with summer temperatures and negatively with spring precipitation. Since 1995, poor reproduction amongst Islay-wintering birds has coincided with increased spring precipitation in the relatively dry interior of west Greenland, where many of these geese nest, and no longer shows any correlation with summer temperature. For geese wintering at Wexford, southeast Ireland, there was also a correlation between reproductive success and summer temperature prior to 1995 and no such relationship afterwards. Although this group of birds similarly shows a negative relationship between reproductive output and the more recent heavy spring precipitation since 1995, this fitness measure amongst Wexford-wintering geese is much lower now than in pre-1995 years, suggesting that factors other than climate have contributed to consistently low reproductive success. Interactions from increasing numbers of Canada Geese breeding and moulting in west Greenland offer one plausible explanation for this phenomenon, but at present there is a lack clear of evidence for this. The recent climate-related changes in the size and success of this population have been incremental. Accelerating melting of the inland ice will lead to substantial increases in the area of the interior lowlands of west Greenland and to changes in the extent and quality of the habitats used by geese that may in the long term be beneficial.